Does It Stand The Time? A Systematic Literature Review on Drilling for Teaching English to Young Learners - Belly Ubaidila; Siti Asmiyah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Drilling may be considered a method of the past within teaching approaches, but it can still be popular in the EFL context, particularly for Teaching English to Young Learners (TEYL). Existing literatures present varying perspectives on the effectiveness of drilling, indicating a need to explore a more comprehensive understanding. This study aims to generally identify the types, advantages, and challenges of drilling used in Indonesian TEYL classrooms to better understand if the drilling is still relevant in the current teaching context. Employing a qualitative approach through a Systematic Literature Review (SLR), data were analyzed from 14 articles selected through predefined inclusion and exclusion criteria. The articles were retrieved using a selection process through Publish or Perish (PoP) from the Google Scholar database and published between 2014 and 2024. Data were analyzed thematically using a table analysis through coding and categorization, covering six main types of drilling: repetition drill, question-and-answer drill, chain drill, single-slot substitution drill, multiple-slot substitution drill, and snowball drilling. The advantages of drilling include increasing student engagement, improving vocabulary mastery, enhancing pronunciation and speaking skills, and supporting learning through multimedia integration. Conversely, challenges involve pronunciation errors, initial lack of engagement, difficulty in memorizing vocabulary, and boredom among advanced learners. The findings suggest that drilling should be integrated with interactive and contextual learning strategies to address the challenges and enhance its effectiveness in modern TEYL settings within the EFL context.